Validation of Decisional Balance and Self-Efficacy Measures for HPV Vaccination in College Women. Issue 5 (May 2013) - Lipschitz, Jessica M.; Fernandez, Anne C.; Larson, H. Elsa; Blaney, Cerissa L.; Meier, Kathy S.; Redding, Colleen A.; Prochaska, James O.; Paiva, Andrea L.
Purpose: Women younger than 25 years are at greatest risk for human papillomavirus (HPV) infection, including high-risk strains associated with 70% of cervical cancers. Effective model-based measures that can lead to intervention development to increase HPV vaccination rates are necessary. This study validated Transtheoretical Model measures of Decisional Balance and Self-Efficacy for seeking the HPV vaccine in a sample of female college students. Design: Cross-sectional measurement development. Setting: Online survey of undergraduate college students. Subjects: A total of 340 female students ages 18 to 26 years. Measures: Stage of Change, Decisional Balance, and Self-Efficacy. Analysis: The sample was randomly split into halves for exploratory principal components analyses (PCAs), followed by confirmatory factor analyses (CFAs) to test measurement models. Multivariate analyses examined relationships between constructs. Results: For Decisional Balance, PCA indicated two 4-item factors (Pros –α = .90; and Cons –α = .66). CFA supported a two-factor correlated model, χ 2 (19) = 39.33; p < .01; comparative fit index (CFI) = .97; and average absolute standardized residual statistic (AASR) = .03; with Pros α = .90 and Cons α = .67. For Self-Efficacy, PCA indicated one 6-item factor (α = .84). CFA supported this structure, χ 2 (9) = 50.87; p < .05; CFI = .94; AASR = .03; and α = .90. Multivariate analyses indicated significant cross-stage differences on Pros, Cons, and Self-Efficacy in expected directions. Conclusion: Findings support the internal and external validity of these measures and their use in Transtheoretical Model–tailored interventions. Stage-construct relationships suggest that reducing the Cons of vaccination may be more important for HPV than for behaviors with a true Maintenance stage.